Evaluation of Development Policy and Increased Integrated Public Transportation in Bandung City - Andrian Surahman; Heru Nurasa; Dadang Enjat Munajat (Green Publisher Indonesia, 2025)
The rapid growth of Bandung, both in population and economic activity, has heightened the demand for efficient and effective transportation. To address these challenges, the Integrated Public Transportation Development and Improvement Policy, grounded in Regional Regulation No. 5 of 2022, was introduced. This study, drawing on Thomas R. Dye's policy implementation theory as referenced by Wahab (2022), aims to assess the effectiveness of this policy in enhancing public transportation services in Bandung. Using a qualitative descriptive analysis method, the research incorporates primary and secondary data gathered through interviews, observations, and document analysis of public transportation systems. The findings reveal that the policy is well-structured with clear objectives, adequate budget allocations, and effective inter-institutional coordination, leading to significant improvements in accessibility and comfort of public transportation. However, challenges remain, including insufficient infrastructure, ineffective regulations, and issues with integrating different transportation modes. The study proposes solutions such as stricter regulation enforcement and better integration of transportation modes. Recommendations include increased infrastructure investment, enhanced coordination among institutions, and greater community involvement in the planning and evaluation processes of public transportation policies. These measures are expected to contribute to a more efficient, effective, and sustainable public transportation system in Bandung, thereby supporting the city’s future development.